Reformasi Birokrasi dan Penerapan Good Government Governance serta implikasinya terhadap Kinerja Pegawai dan Kualitas Pelayanan - Ali Effendi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
The purpose of this research was obtained empirical evidences and found the intelligibility of the phenomenon of the effect of bureaucracy reform, leader skill, and good government governance implementation to employee performance and to observe how it’s implication to service quality. The research was conducted at five one-stop licencing service agencies at four regent, that are Cirebon, Kuningan, Indramayu and Majalengka, and Cirebon City with 120 sample. The research method used descriptive and verification method. The independent variables were : bureaucracy reform (X1), leader skill (X2), and good government governance implementation (X3). Employee performance (X4) as intervening variable and the dependent variable was service quality (Y). SEM analysis was used to examine the models and hypothesis. The result of this research showed that bureaucracy reform significantly affected on employee performance,, leader skill significantly affected on employee performance, good government governance implementation significantly affected on employee performance Employee performance significantly affected on service quality.